Engineering the interactions between a plant‐produced HIV antibody and human Fc receptors. Issue 2 (10th August 2019) - Stelter, Szymon; Paul, Mathew J.; Teh, Audrey Y.‐H.; Grandits, Melanie; Altmann, Friedrich; Vanier, Jessica; Bardor, Muriel; Castilho, Alexandra; Allen, Rachel Louise; Ma, Julian K‐C.
Summary: Plants can provide a cost‐effective and scalable technology for production of therapeutic monoclonal antibodies, with the potential for precise engineering of glycosylation. Glycan structures in the antibody Fc region influence binding properties to Fc receptors, which opens opportunities for modulation of antibody effector functions. To test the impact of glycosylation in detail, on binding to human Fc receptors, different glycovariants of VRC01, a broadly neutralizing HIV monoclonal antibody, were generated in Nicotiana benthamiana and characterized. These include glycovariants lacking plant characteristic α1, 3‐fucose and β1, 2‐xylose residues and glycans extended with terminal β1, 4‐galactose. Surface plasmon resonance‐based assays were established for kinetic/affinity evaluation of antibody–FcγR interactions, and revealed that antibodies with typical plant glycosylation have a limited capacity to engage FcγRI, FcγRIIa, FcγRIIb and FcγRIIIa; however, the binding characteristics can be restored and even improved with targeted glycoengineering. All plant‐made glycovariants had a slightly reduced affinity to the neonatal Fc receptor (FcRn) compared with HEK cell‐derived antibody. However, this was independent of plant glycosylation, but related to the oxidation status of two methionine residues in the Fc region. This points towards a need for process optimization to control oxidation levels and improve the quality of plant‐produced antibodies.